Characterization of Engineering Properties of Active Soils Stabilized With Nanomaterial for Sustainable Infrastructure Delivery - Ugwu, Onuegbu O.; Ogboin, Amadise S.; Nwoji, Clifford U. (Frontiers in Built Environment, 2018)
Nanotechnology has been widely discussed in extant literature as a technological solution to several problems associated with the use of construction materials for sustainable infrastructure delivery. This paper discusses findings from research that investigated applications of Nanotechnology on active soils. It highlights research findings on various areas Nanotechnology can provide innovative solutions for sustainable infrastructure delivery. The research results demonstrate improvements in soil engineering properties that could result from re-engineering construction materials and/or processes. The engineering properties of active soils investigated include: Atteberg Limits (liquid limit - LL, plastic limit - PL etc.), Shrinkage, Dry density Bearing capacity, California Bearing Ratio (CBR), and hydrophobic behavior. Other engineering properties of the active soils investigated include: shrink-swell, water absorption, and activity ratings /classification. The paper uses results from analysis of laboratory tests to discuss improvements in soil engineering properties that result from re-engineering construction materials and processes. Improvements were observed on the engineering properties of soils treated with the nanomaterial. The LL, PL, shrinkage, activity, and CBR showed the following levels of improvement: - 24.21%, 54.02%, -50.24%, -38%, -12,59% and 14% respectively, while the shrink-swell, and water absorption improved by over 60% and 70% respectively. The soils also showed improved hydrophobicity when treated with nanomaterial. The activity ratings transitioned between low, high, and very high depending on the mineralogical and chemical compositions of the soils in their natural states. Statistical tests confirmed that the improvements were attributable to the nanomaterial agent in the active soil samples. However, the statistical tests show that addition of nanomaterial did not have effect on unconfined compressive strength and maximum dry density of the active soil. The paper concludes that given some potential risks in Nanotechnology applications in construction, there is an overarching need to formulate National policies and roadmaps for broader Nanotechnology applications in construction industries at country-specific levels.